Preparation, microstructure and physical characteristics of ferroelectric pb 5 ge 3 O 11 thin films for memory application - Liu, Y. X.; Caragianis-Broadbridge, Christine; Lehman, A. H.; McGuinness, J. K.; Ma, Tso-Ping (MRS Proceedings, 2003)
We report sol-gel process of Pb5Ge3O11 (PGO) as well as the microstructure and physical properties of ferroelectric PGO films for memory applications. The PGO sol was prepared from lead acetate hydrate, germanium isopropoxide, and di(ethylene glycol) ethyl ether. The reactions taking place during the sol-gel process were examined in detail, Diethanolamine (DEA) was added to help maintain the desired species ratio and prevent germanium oxide precipitation. The preferred orientation of the PGO thin films was well controlled by the heating and reflux procedures in the sol-gel preparation process. Additionally, to examine the impact of post-deposition processing, selected samples were oxygen annealed at temperatures ranging from 450-650°C. The samples were characterized with X-ray diffraction (XRD), non-contact (planview) atomic force microscopy (NC-AFM). The resulting data indicate that the microstructure and physical properties of PGO films depend strongly on the precursor preparation as well as the post deposition annealing temperature.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00135 tex.type: [object Object]
Keywords: Atomic force microscopy; Ferroelectric materials; Glove boxes; Isopropoxide; Lead compounds; Low-power memory; MISFET devices; Microstructure; Sol-gels; Thermal effects; Thin films; X ray diffraction; dept.ils

Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (International Conference on Asian Digital Libraries, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils

Transformations of Librarianship in Support of Learning Communities - Sierpe, E.; De la Peña McCook, K. (Reference and User Services Quarterly, 2003)
Keywords: dept.ils; ⛔ No DOI found